Guidelines for preoperative investigations for elective surgery at Queen Elizabeth Hospital: effects on practices, outcomes, and costs - Nicholls, Judith; Gaskin, Pamela S.; Ward, Justin; Areti, Yasodananda K. (Journal of clinical anesthesia, 2016)
We endeavor to assess the impact of introduction of guidelines for preoperative investigations (PIs) on anesthetic practices and costs and compare their efficacy to current practices. A prospective study. Queen Elizabeth Hospital, Barbados. Participants comprised all patients undergoing general, epidural, spinal, and regional anesthesia, with the exception of emergency cases or instances where an anesthesiologist was not required. Introduction of formal guidelines for preoperative investigations. The patterns of preoperative testing were assessed by audit, and this assessment was repeated postintervention. PI guidelines developed were presented to all surgical departments. For younger patients (<60 years), the mean number of tests decreased from 3.42±1.8 in the preguideline group to 2.89±1.98 in the postguideline group (P=.042). The total number of chest x-rays decreased by 14.8% (P=.012) and full blood counts by 7.6% (P=.036). The implementation of PI guidelines led to overall savings of US $7589 per 1000 patients, which is equivalent to (US $40,745.50 per annum). The most notable savings were due to decreased number of chest x-rays. PIs were performed routinely even in the absence of clinical indications. Our findings indicate that introduction of guidelines has reduced the level of preanesthetic investigations to some extent; nevertheless, further change is desirable. In addition, costs to the institution were decreased with no compromise to patient safety. •The introduction of guidelines has resulted in some beneficial changes in practice.•There was a decrease in the numbers of tests done in the younger age groups.•The significant improvements were noted only with full blood count and chest x-ray.•Introduction of guidelines resulted in savings of US $40,745.50 per year.